Spelifiering av processtyrning En studie av ny teknik för webbutveckling - Braaf, Robin (My University, 2014)
This report is the result of a case study of implementing gamification on a process management web service. Node.js which has been studied in the case is a relatively new technology for developing web applications. The report gives an overview about using Node.js as a developer coming from a background in Java and from a business point of view why to choose Node.js as the technology to develop a web application. The case study is material for discussion and more research about how other use Node.js and a comparison with Java EE. The report ends with suggestions on areas for further study and a conclusion about how the environment around Node.js along with its non blocking I/O which makes it a competitive technology.
Keywords: Data- och informationsvetenskap; Computer and Information Science